(untitled) (The Science Post, 2025)
Coronary Heart Disease (CHD) remains one of the most pervasive and fatal cardiovascular conditions globally. With millions of deaths attributed annually to CHD-related complications, accurate and early diagnosis is paramount. Over the years, a range of diagnostic technologies—ranging from traditional electrocardiography (ECG) to sophisticated imaging techniques like cardiac MRI—have evolved to meet clinical needs. This paper provides a theoretical overview of current and emerging CHD diagnostic technologies, highlighting their principles, advantages, and limitations. It categorizes these technologies into non-invasive, minimally invasive, and invasive methods and introduces a theoretical framework to assess their clinical applicability based on accuracy, cost, accessibility, patient safety, and integration potential. Finally, the study discusses challenges in technology adoption, proposes future directions for diagnostic innovation, and suggests strategies for optimizing CHD diagnosis in clinical settings.